Understanding the Challenges Leading to Ineffective Zakat Activities in Zanzibar. Do Political Ideology, Religious Sects, and Ethnicity Matter? - Mjaka Mkuu , Khatib; Effandi Bin Yusoff, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Zakat is a historical nonprofit, faith-based financial instrument, and charity institution for social socialeconomic development and equitable distribution of wealth. Though it has a long history of existence in Zanzibar, zakat failed to deliver at its required level, and scholarly efforts to understand impediments resulting in this failure were imperceptible. This study intends to explore problems and challenges associated with the ineffectiveness of zakat activities in Zanzibar. It is a qualitative multiple case study conducted through in-depth interviews with 12 executives from the five zakat organizations. Based on thematic analysis procedures, these study findings derived three main issues: namely, unsystematic zakat management and administration, lack of proper knowledge and understanding, and the political and regulatory environment are the main impediments for the development and thriving of zakat activities in Zanzibar. With a lack of study in this context, the findings have significantly contributed to the existing body of literature, calling for more studies to elucidate the situation deeply